Surface modification of CoCr alloys by electrochemical reduction of diazonium salts. Issue 41 (2nd July 2018) - Mezour, M. A.; Oweis, Y.; El-Hadad, A. A.; Algizani, S.; Tamimi, F.; Cerruti, M.
Abstract : Tailoring the surface chemistry of CoCr alloys is of tremendous interest in many biomedical applications. Abstract : Tailoring the surface chemistry of CoCr alloys is of tremendous interest in many biomedical applications. In this work, we show that CoCr can be modified by diazonium electrografting provided the surface is not homogeneously covered with an oxide layer. Cyclic voltammetry (CV) and X-ray photoelectron spectroscopy (XPS) show the electrografting of a poly(aminophenylene) (PAP) layer on CoCr when treated at a reductive potential (CoCr−0.5 V ), whereas no PAP film was formed on CoCrOCP and CoCr1 V, treated at open circuit and anodic potentials respectively. Based on XPS results, we attributed the electrografting to the formation of carbide bonds between PAP and the inhomogeneous thin oxide layer of CoCr−0.5 V . We then show an example of application of PAP coatings on CoCr and prove that the presence of a PAP coating on CoCr−0.5 V results in a 5-fold increase of the adherence of poly methyl methacrylate (PMMA) to PAP-coated CoCr compared to uncoated samples; this is of prime significance to improving the long-term stability of dental prostheses. These findings support the importance of reducing the oxide layer for effective functionalization of metal oxides with aryl diazonium salts and suggest a promising surface modification approach for biomedical applications.